Pengungkapan Corporate Social Responsibility (CSR) dan Kinerja Keuangan Perusahaan dengan Pengungkapan Anti Korupsi sebagai Variabel Moderasi - Khamainy, Arief Hidayatullah; Laras Asih, Dessy Novitasari (AKMENIKA, 2019)
The research was carried out to find the influence of training material and methods of training toward workability. The study was conducted respectively from an employee of PD BPR Bantul Yogyakarta. The purpose of this research is expected to be useful for stakeholders in seeing CSR disclosure in the company in testing and analyzing its effect on the company's financial performance and with the presence of anti-corruption exposure, whether it will strengthen the impact of CSR disclosure on the company's financial performance. The study population in this study were all mining companies registered on the Indonesia Stock Exchange in 2016-2018 with a total of 63 companies. The research sample was taken using a random sampling technique that was calculated by the Slovin formula so that 54 samples were obtained for analysis. Linear Regression Analysis and Moderation Regression Analysis were chosen as the analysis technique used in this study. The results show that CSR disclosure does not affect the company's financial performance, and anti-corruption disclosure does not affect the relationship between the two.